Identifikasi Kandungan Metabolit Sekunder dan Uji Aktivitas Antioksidan Ekstrak n-Heksana Kulit Jeruk Bali (Citrus maxima Merr.). - Elisabeth Oriana Jawa La; Repining Tiyas Sawiji; Ni Made Rai Yuliani (Jurnal Surya Medika (JSM), 2021)
Degenerative diseases triggered by antioxidants in the body are unable to neutralize the increased concentration of free radicals that can cause cell damage, so to destroy free radicals it is necessary to have antioxidants from outside the body. Grapefruit peel (Citrus Maxima Merr) is one plant that is known to have a lot of secondary metabolite content however it is not fully utilized. To analyze the content of chemical compounds and the antioxidant effect of n-hexane extract of Grapefruit peel (Citrus Maxima Merr.). Identification of chemical compounds was carried out by phytochemical screening and confirmed by the analysis of the extract thin layer chromatography profile, whereas the antioxidant activity test was carried out using the radical capture method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) with Trolox as a comparison. The results of the identification of Grapefruit peel (Citrus Maxima Merr) extracts is containing secondary metabolites in the form of flavonoids, saponins, alkaloids, triterpenoids/steroids, and tannins. The results of antioxidant activity test extracts of grapefruit peel(Citrus Maxima Merr) and Trolox each showed values that: IC50 111.69 ppm and 12.143 ppm. From the results of this test, the extract of grapefruit peel (Citrus Maxima Merr) has moderate antioxidant activity when compared to Trolox.